2010
DOI: 10.1063/1.3530013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanorods for Optofluidic Applications

Abstract: We have developed a method for laser beam manipulation by using a colloid of nickel nanorods produced by electroplating chemistry. It is shown that the shape of the laser beam passing through a colloid of nickel nanorods can be altered by varying the applied magnetic field. This effect is caused by multiple scattering and diffraction of the laser beam by the nanorods. Compared with spherical nanoparticles, magnetic nanorods are better suited for illumination applications because they are stable in a rotating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 12 publications
(24 reference statements)
1
33
0
Order By: Relevance
“…A few millitesla fields are sufficient enough to rotate magnetic nanoparticles. 8,21 In our experiments, we examined the performance of four, three, and two magnetic coils. The software developed in LABVIEW is able to produce three types of magnetic fields: rotating, pulsating, and dc fields.…”
Section: Design Of the Magnetic Rotatormentioning
confidence: 99%
See 3 more Smart Citations
“…A few millitesla fields are sufficient enough to rotate magnetic nanoparticles. 8,21 In our experiments, we examined the performance of four, three, and two magnetic coils. The software developed in LABVIEW is able to produce three types of magnetic fields: rotating, pulsating, and dc fields.…”
Section: Design Of the Magnetic Rotatormentioning
confidence: 99%
“…Therefore, knowing the critical frequency and geometrical parameters of the nanorod, one can measure either fluid viscosity (provided that the magnetic moment M is known) or the nanorod magnetic moment (provided that the fluid viscosity is known). 8,15 Equation (7) is the fundamental equation of magnetic rotational spectroscopy (MRS) for the analysis of viscous fluids with nanorods. 15,37 …”
Section: Fig 3 Integral Curves Of Eq (4) Showing the Solution Behamentioning
confidence: 99%
See 2 more Smart Citations
“…For a ferromagnetic nanowire, researchers have shown that the magnetic torque could be quantitatively calculated [7][8][9]. However, there were different models to compute the fluid torque [10][11][12]. In previous studies,…”
Section: Introductionmentioning
confidence: 99%